Hubungan Antara Pola Asuh Orang Tua Di Rumah Bentuk Authoritative Terhadap Pembentukan Perilaku Sosial Anak Pada Siswa Kelas IV SD - Dewa Ayu Ketut Cintya Wulandari; IGA. Ayu Wulandari; D.B. Kt. Ngr. Semara Putra (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2022)
This study aims to determine the relationship between parental parenting at home in an authoritative form with children's social behavior in grade IV students of SD Cluster IV, State District for the 2022/2023 School Year. This type of research is ex post facto correlational. The population of this study is all grade IV students of SD Cluster 4 State District for the 2022/2023 School Year, which amounts to 242 students. The study sample totaled 148 students. The sample determination technique used is a proportional random sampling technique. The data collected are quantitative data with interval scales, namely authoritative parenting and social behavior, data collection methods using non-test methods. Data on authoritative parenting and social behavior were obtained through questionnaires/ questionnaires. The statistical analysis used in the study is product moment correlation analysis. The results showed that there was a significant relationship between parental parenting at home authoritative form and children's social behavior obtained r count = 2,826 and rtable at the level of significance (α = 0.05 n = 148) So it can be concluded that there is a significant relationship between parental parenting at home authoritative form on children's social behavior in grade IV students at SD Cluster 4 State District for the 2022/2023 School Year.